Розробка та реалізація комплексу регіональних та місцевих програмних заходів розвитку малого та середнього підприємництва - Кропівний, В. М.; Будулатій, В. В.; Травкіна, Н. М.; Kropivnyі, V.; Budulatiy, V.; Travkina, N. (ЦНТУ, 2017)
В статті аналізуються тенденції та показники розвитку малого та середнього бізнесу в Кіровоградському регіоні. Розглянуті механізми державної політики підтримки на місцевому рівні бізнесового середовища, зокрема регіональна програма розвитку малого та середнього підприємництва у Кіровоградській області на 2016-2018 роки. Здійснено узагальнення результатів виконання Програми, визначені основні проблеми, що стримують розвиток підприємництва в регіоні та визначені пріоритетні завдання Програми на наступний період. In order to identify the main reasons that hinder small and medium entrepreneurship development in the region and determine the priority directions of their development, the analysis is made and trends and indicators of SME development in Kirovohrad region are generalized, the mechanisms of the state policy of support at the local level of the business environment are defined, in particular through the implementation of the measures of the regional program of small and medium entrepreneurship development in Kirovohrad region in 2016, the main reasons that hinder the development of entrepreneurship in the region are identified and the priorities of this program for the next period are determined. An analysis of the indicators of SMEs development in Kirovohrad region showed that the general tendency of the dynamics of business entities activity in Kirovohrad region has been improved. However, under present conditions, SMEs are faced with a multitude of constraining factors and problems that have to be tackled on their own. In order to solve the problems, identified during the implementation of the program of the small and medium entrepreneurship development of Kirovograd region for 2016-2018 and the programs of all previous periods, it is expedient to develop and implement such program for a five-year period, taking into account the economic and innovative potential of the region, and to introduce the development of the Concept/Road map for the small and medium entrepreneurship development in Kirovograd region for the period up to 2022.
Development and implementation of the complex of regional and local program measures for small and medium entrepreneurship development
Keywords: державна політика; підтримка; малий і середній бізнес; підприємницька діяльність; регіон; програма; розвиток; state policy; support; small and medium entrepreneurship; entrepreneurial activity; region; program; development